The good, the loyal or the active? MPs' parliamentary performance and the achievement of static and progressive career ambitions in parliament. Issue 4 (10th November 2022) - Schobess, Richard; de Vet, Benjamin
Abstract: Although often theorized, empirical research on the relationship between MPs' parliamentary behaviour and their chances to realize career ambitions is relatively scarce. This article holistically analyses the effect of MPs' (1) party loyalty, (2) activity level and (3) the quality of their parliamentary work on MPs' prospects for re-election and their promotion to higher parliamentary office. Based on a unique combination of behavioural and peer assessment data on 325 federal and regional MPs in Belgium (2014–2019), we find that particularly MPs' loyalty and activity level improve their career prospects in the subsequent term, in contrast to more qualitative aspects of their parliamentary work. These findings provide important new insights into how and to what degree legislators are rewarded for their parliamentary performance.